Economic analysis and spatial arrangements of engineering SMEs performance in Olomouc region of Czech Republic - Lucie Meixnerová; Michal Menšík; Vít Pászto (Journal of International Studies)
The aim of this paper is to describe SMEs performance on the regional level with respect to their geographical location. As there is no such research on the regional level, we calculate and describe traditional indicators of performance, financial position and changes in the financial position represented by ROE, Financial Leverage and Cash Flow on Sales. These indicators are then compared with the results of previous research which has been conducted on Eastern Europe and also spatially projected on the map to demonstrate spatial distribution of companies’ performance. Our findings from the observation of 170 SMEs allow us compare the regional level of financial indicators with the European one, and our findings suggest that the Olomoucký region is weaker.